Women’s Self-Expression in the Abbasid Era Ulayya Bint Al-Mahdi and Assia Baghdadi as an Example - Bazuhaır, Narjees Abdulgaffar Said (Journal of Arabic Language Sciences and Literature, 2022)
The self-expression issue basically represents one of the elements that shape the identity of the person in general, and the writers and poets in particular; as the writer does not only represent his/her identity, but also the identity of his/her time through the public societal or private humanitarian issues he/she presents. Literary works are essentially psychological components that stir emotions, stimulate reactions, and ultimately express a stance, or lead to judgments, through which we can study entire eras. Women are considered an important part of this issue in terms of their excellence in a special expression style; which is sometimes similar to that of the master writers and poets, while differs from them at other times, and that style is characterized by features that have disappeared among men in many cases; and so we see “Ulayya Bint Al-Mahdi” and “Assia Baghdadi” as two examples expressing this excellence.
Keywords: Literature; Poetry; Women; Expression; Self; Psychological Image; Ulayya Bint Al-Mahdi; Assia Baghdadi